Efficacy of Sound, Power, Potency and Promise in the Translocal Ritual Music of Cuban Ifa-Orisa - Gibbs, Tanesha (International Library of African Music, 2025)
pages: 77-80
Keywords: Book reviews; Ritual; Orisha religion; Yoruba (African people)--Religion; Ritual Music; Religious Authenticity; Nigeria; Ifa-Orisa; Cuba; Cuban Ifa-Orisa; Yoruba Art; African Music